Analysis of antibiotic resistance genes in pig feces during the weaning transition using whole metagenome shotgun sequencing - Gi Beom Keum; Eun Sol Kim; Jinho Cho; Minho Song; Kwang Kyo Oh; Jae Hyoung Cho; Sheena Kim; Hyeri Kim; Jinok Kwak; Hyunok Doo; Sriniwas Pandey; Hyeun Bum Kim; et al. (Journal of Animal Science and Technology, 2023)
Antibiotics have been used in livestock production for not only treatment but also for increasing the effectiveness of animal feed, aiding animal growth, and preventing infectious diseases at the time when immunity is lowered due to stress. South Korea and the EU are among the countries that have prohibited the use of antibiotics for growth promotion in order to prevent indiscriminate use of antibiotics, as previous studies have shown that it may lead to increase in cases of antibiotic-resistant bacteria. Therefore, this study evaluated the number of antibiotic resistance genes in piglets staging from pre-weaning to weaning. Fecal samples were collected from 8 piglets just prior to weaning (21 d of age) and again one week after weaning (28 d of age). Total DNA was extracted from the 200 mg of feces collected from the 8 piglets. Whole metagenome shotgun sequencing was carried out using the Illumina Hi-Seq 2000 platform and raw sequence data were imported to Metagenomics Rapid Annotation using Subsystem Technology (MG-RAST) pipeline for microbial functional analysis. The results of this study did not show an increase in antibiotic-resistant bacteria although confirmed an increase in antibiotic-resistant genes as the consequence of changes in diet and environment during the experiment.